Regeneration of full-length layers cartilage in experimental under the impaction platelet rich plasma - Vernygorodskyi, Sergiy; Fishchenko, Volodymyr; Rybinskyi, Maksym (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
It is known that even small damage to the cartilage, regardless of genesis, is not spontaneously repaired. This provokes in the future the spread of degenerative joint damage and the occurrence of irreversible secondary arthrosis changes. Objective: to analyze the effect of autologous platelet rich plasma on the regeneration process in simulated cartilage defects in the intercondylar region of the femur in rabbits, to evaluate the microscopic pattern at different time intervals, to identify possible disadvantages and complications of the technique. Methods: the experiment was conducted on 24 adult rabbits. Defects were created in the intercondylar area of the distal femur of both extremities: with involvement of the subchondral plate before the appearance of blood dew — 12 defects in the main group and 10 in the control group, without its involvement — 12 and 10, respectively. On the 7th d ay a fter t he o peration, p latelet r ich p lasma w as injected into the joints of the control group rabbits. In 2 animals (intact), the knee joints were not injured. After 2, 4 and 8 weeks, a macroscopic and histological analysis of the formed regenerate was carried out. Results: 8 weeks after the operation, the average thickness of the regenerate in animals with damage to the subchondral plate was (0.34 ± 0.06) mm in the main group and (0.58 ± 0.009) mm in the control group. Without damage to the subchondral plate, the regeneration of the cartilaginous tissue is limited and after 8 weeks is practically not observed even when using platelet rich plasma. Regenerate in the main group was a fibrous-cartilaginous structure with signs of differentiation of chondroblasts, in control — fibrous, with a large number of vessels. Conclusion: the structure of the regenerate in the defects of the articular cartilage with the involvement of the subchondral plate proved to be qualitatively better in the subgroup of animals that received platelet rich plasma in the postoperative period.